Randomized controlled trial of social cognition and interaction training compared to befriending group. (8th June 2020) - Dark, Frances; Scott, James G.; Baker, Andrea; Parker, Stephen; Gordon, Anne; Newman, Ellie; Gore‐Jones, Victoria; Lim, Carmen C. W.; Jones, Lyndall; Penn, David L.
Abstract : Background: Deficits in social cognition are common in people with schizophrenia and are associated with impaired functioning. Finding effective interventions to address these deficits is a priority. Social Cognition Interaction Training (SCIT) is a psychosocial intervention that has demonstrated acceptability and feasibility in various health care settings. Larger, well‐designed randomized controlled trials are needed to examine the effectiveness of this intervention. Design: A randomized controlled trial. Methods: One hundred and twenty adults diagnosed with schizophrenia spectrum disorder were randomized to receive SCIT ( n  = 61) or Befriending Therapy (BT) ( n  = 59). Both intervention groups were delivered weekly for 2 hr over 12 weeks. Neurocognitive assessment was completed at baseline. Participants completed assessments of social cognition, social functioning, and meta‐cognition at baseline, post‐intervention, and 3‐month follow‐up. Results: There were no clinically significant differences between group outcomes on any measure of social cognition or social functioning. There was a trend for both groups to improve over time but not at a level of statistical significance. Conclusions: SCIT did not show any additional benefits on measures of social cognition compared to Befriending Therapy for people with schizophrenia spectrum disorder. The findings are discussed in terms of potential improvements to the programme. Practitioner points: Effective interventions for the social cognitive deficits of schizophrenia spectrum disorders are still being refined. Social Cognition Interaction Training is a promising therapy but requires further modifications to improve its effectiveness.